2009
DOI: 10.1172/jci37209
|View full text |Cite
|
Sign up to set email alerts
|

Prolylcarboxypeptidase regulates food intake by inactivating α-MSH in rodents

Abstract: The anorexigenic neuromodulator α-melanocyte-stimulating hormone (α-MSH; referred to here as α-MSH 1-13 ) undergoes extensive posttranslational processing, and its in vivo activity is short lived due to rapid inactivation. The enzymatic control of α-MSH 1-13 maturation and inactivation is incompletely understood. Here we have provided insight into α-MSH 1-13 inactivation through the generation and analysis of a subcongenic mouse strain with reduced body fat compared with controls. Using positional cloning, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
175
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(184 citation statements)
references
References 31 publications
7
175
0
2
Order By: Relevance
“…Furthermore, prolylcarboxypeptidase have been shown to regulate food intake by inactivating -MSH centrally. It is plausible that similar mechanisms might regulate effects of the melanocortin system in the periphery (Wallingford et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prolylcarboxypeptidase have been shown to regulate food intake by inactivating -MSH centrally. It is plausible that similar mechanisms might regulate effects of the melanocortin system in the periphery (Wallingford et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Another family member, prolyl endopeptidase (PREP), has a high degree of sequence similarity, and is phylogenetically close to PRCP (22). PREP cleaves known PRCP substrates angiotensin (Ang) II/III and ␣-melanocyte stimulating hormone (MSH) (23,24), as well as neurotensin (NTS), cholecystokinin, and gastrin-releasing peptides (25). These peptides are ligands for a number of G-protein coupled receptors (GPCR) such as angiotensin receptors and neurotensin receptors which can cross talk with IR/IGF-1R, and play a critical role in pancreatic cancer development in animal models (26,27).…”
mentioning
confidence: 99%
“…7, a region contained within the confidence intervals of previously (see Kelly et al 2010b) identified QTL for running distance and duration (see Figure 3C and Kelly et al 2010b). Wallingford et al (2009) observed that the inhibition of Prcp activity in vivo decreased food intake in wild-type and obese mice, and Prcp-null mice were leaner and shorter than wild-type controls and resistant to high-fat diet-induced obesity (Wallingford et al 2009). Similar phenotypes have been observed in the HR strain of mice utilized here (Swallow et al 1999;Kelly et al 2006;Vaanholt et al 2008).…”
Section: Identification Of Potential Candidate Genesmentioning
confidence: 65%